2014
DOI: 10.1080/02681102.2013.874315
|View full text |Cite
|
Sign up to set email alerts
|

The Information Technology Influence on LIS Job Descriptions in South Africa

Abstract: IT (information technology) and its association with communication technology (information and communication technologies (ICTs)) have changed the way libraries operate. Today, ICTs play a very important role in the library environment. Traditional library tasks such as cataloguing, circulation, and collection development, which were performed manually a few decades ago, have now been automated to a lesser or greater extent. This has led to changes in some library and information science (LIS) job titles and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…Emeh and Agbor suggested that, in order to prepare and produce teachers who are valid and relevant for information age, the government should be endeavor to re-build teacher self-image, and to stress the cultural framework within which the information age operates' (Emeh & Agbor,2003). The suggested strategies and solutions were also in agreement with current studies such those of Muhametjanova & Cagiltay (2016), Shongwe (2015), Tabira & Otieno (2017) and Jaarsveldt & Wessels (2015).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Emeh and Agbor suggested that, in order to prepare and produce teachers who are valid and relevant for information age, the government should be endeavor to re-build teacher self-image, and to stress the cultural framework within which the information age operates' (Emeh & Agbor,2003). The suggested strategies and solutions were also in agreement with current studies such those of Muhametjanova & Cagiltay (2016), Shongwe (2015), Tabira & Otieno (2017) and Jaarsveldt & Wessels (2015).…”
Section: Discussionsupporting
confidence: 77%
“…From these above statements teachers suggested that the government should (1) train them to gain the required knowledge, (2) support them by having their own laptops, (3) provide required infrastructures (4) recruit other teachers to reduce teachers-learners ratio and finally (5) increases teachers motivation by reducing all challenges attached to the shortage of financial payments. These findings were also identified in other related studies such as those of Helm (2015), Porter & Graham (2016), Muhametjanova & Cagiltay (2016), Shongwe (2015), Tabira & Otieno (2017) and Jaarsveldt & Wessels (2015). From above statements it is well observed that teachers' perception towarded the implementation of OLPC program helped them to recognize the contribution of different stakeholders in primary schools.…”
Section: ……The Government Should Facilitate Teachers To Gain More Ssupporting
confidence: 65%
“…(3) increase socialization to improve the mindset of educators so that they are not only teaching for knowledge, but directing for skills; and (4) prepare teachers relevant to 21 st century skills by promoting cultural character and increasing digital literacy. The idea of innovation is supported by previous studies by Jaarsveldt & Wessels (2015); Muhametjanova & Çagiltay (2012); Shongwe (2015) that in improving the quality of teachers in developing countries, and preparing teachers relevant to developments in the information era, the government should rebuild the self-image of teachers and emphasize cultural order as a guideline to facing the information era.…”
Section: Integrating Digital Technologymentioning
confidence: 97%
“…The two authors probably meant “smart” technologies or AI or super computers as computers have been with us since the mid-20th century. An important study conducted in this decade (Ocholla and Shongwe, 2013) demonstrates a diversification in the employment of LIS graduates, with emerging disciplines/fields, such as information and knowledge management, becoming increasingly attractive while ICT’s influence on LIS jobs burgeoning (Shongwe, 2015).…”
Section: Frameworkmentioning
confidence: 99%